2013
DOI: 10.1177/0333102413491028
|View full text |Cite
|
Sign up to set email alerts
|

Successful therapy for temporomandibular pain alters anterior insula and cerebellar representations of occlusion

Abstract: Our findings highlight the impact of the anterior insula for the internal monitoring and the anticipation of temporomandibular joint (TMJ) pain. In addition, an increase of symmetry of condylar movements after therapy has been associated with a decrease of activation magnitude in primary motor and cerebellar regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 35 publications
1
41
0
5
Order By: Relevance
“…In the present study, we observed the changes after a routine treatment period of 3 months when the TMDs symptoms and signs had generally subsided, as indicated by the Di index. Furthermore, the previous study did not include a control group (Lickteig et al , ); therefore, it is difficult to determine whether the decreased activation in the cerebellum after splint treatment was normalization.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study, we observed the changes after a routine treatment period of 3 months when the TMDs symptoms and signs had generally subsided, as indicated by the Di index. Furthermore, the previous study did not include a control group (Lickteig et al , ); therefore, it is difficult to determine whether the decreased activation in the cerebellum after splint treatment was normalization.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the neural recovery associated with increased activation in these regions might have been enhanced with the positive somatosensory input because the splint treatment creates a beneficial environment for occlusion, muscle activity and TMJ movements. One previous study revealed decreased activation in the cerebellum during occlusion following splint therapy for patients with craniomandibular disorders (Lickteig et al, 2013). This difference may be explained by the fact that the previous study was executed during changes in pain processing and during a shorter duration of 14 days.…”
Section: Post-treatment Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…First, it was planned as an exploratory study with a limited sample size even though it is not far from sample sizes described in recent neuroimaging studies of orofacial pain conditions. 5961 This may explain why differences in brain activation spatial extent did not reach significance between PDAP patients and controls matched to stimulus intensity, as well as why only a fixed-effects model (within-subject variability) showed significant differences in brain activations between groups. Mixed-effects analysis results that use subject-to-subject variation (cross-subject variability) as a measure of variance were also reported, which allows inferences based on it to be extrapolated to the population level.…”
Section: Discussionmentioning
confidence: 99%
“…Já o estimulo doloroso dental levou a ativação do S1 bilateral e do córtex motor primário (M1) ipsilateral (Jantsch et al, 2005). (Lickteig et al, 2013).…”
Section: Revisão De Literaturaunclassified